Unburied Lives : The Historical Archaeology of Buffalo Soldiers at Fort Davis, Texas, 1869-1875 - Wilkie, Laurie A., 1968- (Book collections on Project MUSE., 2021)
In Unburied Lives Wilkie demonstrates how we can "listen" to stories found in things neglected, ignored, or disparaged--documents not consulted, architecture not studied, material traces preserved in the dirt